The political economy of International Finance Corporation lending - Dreher, Axel; Lang, Valentin; Richert, Katharina (Journal of development economics, 2019)
Much of the International Finance Corporation's (IFC) lending benefits private companies from rich countries and supports projects in middle-income countries. Large corporations such as Lidl or Mövenpick have received its loans for highly profitable investments. This contrasts to some extent with the IFC's official mandate, which is to finance poverty-reducing projects for which private capital is not available on reasonable terms. Investigating a potential driver of this mismatch, we argue that some governments can influence the allocation of IFC loans to the benefit of private companies in their countries. Using new data for more than 3000 IFC projects over the 1995-2015 period we show that (joint) IFC Board membership of countries where borrowing companies are based and of countries where the projects are implemented increases the likelihood that these countries receive IFC loans. This has implications for the debate on leveraging private-sector investments for development.
Gesehen am 02.09.2019